2017
DOI: 10.1016/j.acclit.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of specialists on audit engagements: A research synthesis and directions for future research

Abstract: This synthesis covers academic research on the use of valuation, tax, information technology (IT), and forensic specialists on audit engagements. The importance and role of specialists on audit engagements have recently increased, and specialist use has garnered significant attention from regulators and academics. Given the PCAOB’s (2017b) recent proposal to revise auditing standards regarding specialists’ involvement, it is important to review the specialist literature as a whole. By integrating research acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…Similarly, previous research has also found evidence that proximity of an ME to the audit client and the sourcing of an ME can influence auditors' judgments and decisions (Griffith, 2015;Weisner & Sutton, 2015). Limited research in the area and continual deficiencies observed by the ASIC in auditors' evaluations of MEs' capabilities makes it necessary to extend the body of existing research and identify other factors that could potentially influence auditors' reliance or trust in MEs or alter their reliance decisions (Hux, 2017). One can infer from these studies that the use of MEs and characteristics of MEs can influence auditors' judgments and decisions.…”
Section: The Asic -The Regulatormentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous research has also found evidence that proximity of an ME to the audit client and the sourcing of an ME can influence auditors' judgments and decisions (Griffith, 2015;Weisner & Sutton, 2015). Limited research in the area and continual deficiencies observed by the ASIC in auditors' evaluations of MEs' capabilities makes it necessary to extend the body of existing research and identify other factors that could potentially influence auditors' reliance or trust in MEs or alter their reliance decisions (Hux, 2017). One can infer from these studies that the use of MEs and characteristics of MEs can influence auditors' judgments and decisions.…”
Section: The Asic -The Regulatormentioning
confidence: 99%
“…One can infer from these studies that the use of MEs and characteristics of MEs can influence auditors' judgments and decisions. Limited research in the area and continual deficiencies observed by the ASIC in auditors' evaluations of MEs' capabilities makes it necessary to extend the body of existing research and identify other factors that could potentially influence auditors' reliance or trust in MEs or alter their reliance decisions (Hux, 2017).…”
Section: The Asic -The Regulatormentioning
confidence: 99%
“…Specialists in law, valuation, IT, and other areas have been increasingly hired by accounting firms to perform an expanding set of non‐audit services (Malsch and Gendron ). Due to increased complexity in these areas within audit clients' business processes and financial statements, these specialists also now assist auditors extensively in performing the audit (EY 2012; PwC ; Hux ) and typically work in the same office (or at least the same country) as the auditors they assist.…”
Section: Context and Theory Developmentmentioning
confidence: 99%
“…The limited audit literature on teams focuses on the audit team made up of only auditors (Rich et al 1997;Nelson and Tan 2005); this team is seen as "the basic operating unit that performs audit work" (Rudolph and Welker 1998, 1), with technical specialists seen as firm members outside the audit team (Bobek et al 2012). At best, IT specialists are seen as consultants sometimes and as audit team members at other times (Curtis et al 2009;Boritz et al 2017;Hux 2017). Further, how recent studies view IT (and other) specialists is not much different from how earlier studies do-as individuals outside the audit team whom auditors consult with to obtain information and reduce uncertainty in auditor decisions (Danos et al 1989;Rudolph and Welker 1998).…”
Section: Audit Teams Auditors and It Specialists: One-team Versus Tmentioning
confidence: 99%
“…Despite the growing attention to auditors' use of MEs' work from the regulators, standard setters, professional bodies and researchers, continually observed audit file deficiencies suggest a critical need for further research in relation to auditors' use of the work of MEs. Studies have particularly called for future researchers to identify various expert‐specific, environmental, regulatory or firm‐specific factors (Hux, 2017) that may influence audit planning judgements (Messier, 2010), actual audit evidence decisions (Brown‐Liburd et al, 2014) and the resolution of inconsistent audit evidence (Griffith, 2015).…”
Section: Introductionmentioning
confidence: 99%